Prognostic Value of Gastrokine-2 (GKN2) and Its Correlation with Tumor-Infiltrating Immune Cells in Lung Cancer and Gastric Cancers - Liu F; Wu H (Dove Medical Press, 2020)
Fangteng Liu,1,2 Hengyu Wu1 1Department of Breast Surgery, The Third Hospital of Nanchang, Nanchang, Jiangxi 330009, People’s Republic of China; 2Faculty of Medicine, University of Munich, Munich 80336, GermanyCorrespondence: Hengyu Wu Tel +86-15270280590Email why_wuhengyu0590@163.comBackground: GKN2, as a secretory protein, is involved in the inflammation and immune modulation, and its aberrant expression is closely related to tumorigenesis. However, integrated studies on the value of GKN2 as a promising clinical biomarker and immunotherapy target in multiple tumors are still rare.Methodology: Multiple online databases, including ONCOMINE, SEGreg, UALCAN, GEPIA, K-M Plotter, cBioPortal, MethSurv, CellMarker, and Timer, were applied to assess the clinical significance of GKN2 and its correlation with tumor-infiltrating immune cells in differentially expressed cancers.Results: Several databases confirmed that GKN2 was significantly down-regulated in lung and gastric cancers compared that in normal samples. GKN2 was altered in 3%, 5%, and 4% of the LUAD, LUSC, and STAD samples, respectively. Hyper-methylation of GKN2 was found in LUAD and LUSC samples. For the clinical values of GKN2, we found that the low transcription level of GKN2 was associated with worse OS in lung cancer, and inferior FP and PPS in gastric cancer, and the relationships between GKN2 expression and clinical variables regarding OS/FP/PPS in lung and gastric cancers were assessed. Moreover, the prognostic value of the DNA methylation patterns of GKN2 in LUAD, LUSC, and STAD was identified. Furthermore, GKN2 expression was found to be significantly correlated with the infiltrating multiple tumor immune cells, and statistically significant differences in the correlation between GKN2 expression and multiple markers of neutrophils and macrophage polarization were observed in LUAD, LUSC, and STAD.Conclusion: The study revealed the prognosis and risk factors for deterioration in patients with low expression of GKN2. GKN2 may be used as a valuable prognostic biomarker and therapeutic target in lung and gastric cancers.Keywords: GKN2, lung cancer, gastric cancer, prognosis, tumor-infiltrating, biomarker